Destination characteristics influence domestic tourists’ decision to choose a destination: Empirical study in Phu Yen-Vietnam - Viet, Ha Nguyen Thi (Journal of Tourism Management Research, 2024)
The study aims to assess how destination characteristics affect site selection behavior, and visitor loyalty, thereby identifying motivating and limiting factors to make recommendations to guide destination policies. The characteristics of the destination are one of the factors affecting the choice of travel destination for tourists. However, each location must identify outstanding features to exploit to create a comparative advantage in attracting tourists toward sustainable development. Drawing upon consumer behavior theory, this research explores the factors that shape tourists’ destination choices. These factors include internal factors (motivational drivers) and external factors (encompassing the destination’s appealing characteristics). Data was obtained from a questionnaire given to tourists who had traveled to Phu Yen between June and August 2023. Data collected from 226 visitors selected using convenience sampling techniques was processed and analyzed using Smart-PLS software. The research results show that destination characteristics, including tourism resources and infrastructure, positively influence tourists’ self-motivation to learn about the culture and history here. We suggest that tourism managers and businesses should enhance tourism in Phu Yen to attract new tourists and encourage them to return. It is crucial to focus on promotion to make visitors aware of Phu Yen’s unique characteristics and to improve infrastructure to make it easier for tourists to access services.